Willingness to Communicate in English in Relation to Language Use and Motivational Orientations among Pakistani Undergraduates - Ubaid, Ullah (Universiti Malaysia Sarawak, 2023)
The current study aimed to investigate Pakistani undergraduates’ willingness to communicate (WTC) in English inside the classroom in relation to language use outside the classroom, motivational orientations to learn English, and the teachers’ views about their undergraduates’ WTC in English inside the classroom. Three theories i.e., sociocultural theory, domains of language use, and socio- psychological were combined to examine the complex construct of situational L2 WTC. Using a quantitative survey research design, this study recruited 450 undergraduates and 80 ESL teachers through the cluster sampling method from eight universities in the Khyber Pakhtunkhwa province of Pakistan. Data were collected through questionnaires constructed from previous studies. The findings revealed that the participants’ level of WTC in English was high in most of the classroom situations including grouping mode, activities (role-play, discussion, and presentation), when given preparation time, with the same gender, and while sitting in front of the class. On the other hand, their level of WTC was moderate in some situations i.e., with the opposite gender, while sitting in the middle and at the back of the classroom, and in front of the whole class. The data obtained from the domains of language use outside classroom revealed that the participants used the Pashto language most frequently in the family, neighbourhood and friendship, and religion domains. Urdu was the most frequently used language in educational and transactional domains, while English was predominantly used in mass media and social media domains. The data also revealed that WTC in English inside the classroom was significantly positively correlated with English language use outside the classroom in friendship and neighbourhood, educational, transactional, and social media domains. While there was a significant but negative correlation between WTC in English and English language use in the religious domain. Conversely, English language use in the family and mass media domains was not significantly correlated. It was found that the participants were highly integratively and instrumentally motivated to learn English. The results also showed that both integrative and instrumental motivational orientations were significantly positively correlated with WTC in English. The findings from teachers’ perspectives revealed that the undergraduates’ level of WTC in English was high in most of the situations including same and opposite genders when given preparation time while sitting in the middle of the class, and front of the whole class. Conversely, the participants’ level of WTC was moderate in the classroom situations i.e., grouping mode, during activities, while sitting in the middle, and at the back of the class. The results on the relationship between the undergraduates’ WTC and the teachers’ views about their WTC inside the classroom in various situations revealed that there was no significant correlation in all nine situations including grouping mode, activities, and the same and opposite gender, when given preparation time, seating position (in front, in the middle, and at the back of the class), and in front of the whole class. This study revealed that WTC is not only influenced by linguistic, and psychological factors but also physiological and social factors. It can be argued that social interactions among peers inside the classroom can enhance the learners’ WTC in English. Also, exposure to the English language outside the classroom and motivation can positively influence the students’ WTC in English